The Influence Of Employer Branding And Company Reputation On Generation Z's Intention To Apply: A Case Study On Management Undergraduate Students At Universitas Pamulang - Yunanti, Siska; Andi, Dede; Wiguna, Melda (Sean Institute, 2025)
The purpose of this study is to determine the effect of employee branding and corporate reputation on the intention to apply among Generation Z students (a case study of Management Program students at Universitas Pamulang), both partially and simultaneously. The research method used is quantitative with an associative quantitative approach. The population consists of a group of individuals, and data collection is carried out using questionnaires. The data analysis techniques include validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing, supported by the Statistical Product and Service Solutions (SPSS) program. The results show that employee branding significantly influences the intention to apply. This is evidenced by the statistical analysis, which demonstrates a strong relationship and a substantial contribution of employee branding to the intention to apply. Similarly, corporate reputation also significantly affects the intention to apply, supported by strong statistical relationships and a meaningful contribution. Simultaneously, employee branding and corporate reputation have a significant effect on the intention to apply. This conclusion is supported by the results of hypothesis testing, showing a very strong relationship and a considerable contribution of these factors to the intention to apply. The study concludes with a regression equation demonstrating the relationship between the variables